Tungiasis: a case report - Valentín, Sheila M.; Sánchez, Jorge L.; Hillyer, George V.; Vélez, Rafael (Puerto Rico Health Sciences Journal, 2007)
This is a case report of a patient who developed a nodule in one foot, which upon biopsy, was diagnosed as tungiasis, a cutaneous infestation caused by a human flea. The natural life cycle, clinical and pathological expressions are discussed.